1999
DOI: 10.1002/(sici)1521-4141(199912)29:12<3914::aid-immu3914>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of T cell proliferation through CD28 induces GATA‐3 and promotes T helper type 2 differentiationin vitroandin vivo

Abstract: The relative contribution of T cell receptor‐versus CD28‐mediated signals in co‐stimulation of resting CD4 T cells is thought to influence their functional differentiation towards T helper (Th) 1 versus Th2 subsets. We have used a conventional and a mitogenic CD28‐specific monoclonal antibody to assess the effect of polyclonal T cell activation through CD28 alone on CD4 subset differentiation. In vivo, mitogenic but not conventional anti‐CD28 induces massive lymphocytosis, the Th2 cytokines interleukin (IL)‐4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This might be explained by the observation that at least during thymic development GATA-3 expression raises during stages of high proliferation (45). Moreover, it has been reported that a polyclonal stimulation of CD4 + T cells increases GATA-3 expression (46). Hence, under the influence of ConA DON may again increase further the expression of a transcription factor, which is already induced by the polyclonal stimulation of the T cells in the PBMC-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the observation that at least during thymic development GATA-3 expression raises during stages of high proliferation (45). Moreover, it has been reported that a polyclonal stimulation of CD4 + T cells increases GATA-3 expression (46). Hence, under the influence of ConA DON may again increase further the expression of a transcription factor, which is already induced by the polyclonal stimulation of the T cells in the PBMC-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been reported that CD28-costimulation induces GATA3 expression and Th2 differentiation via the activation of NFκB [41,42]. Additional studies in mice revealed that PKCθ is involved in mounting both Th2- and Th1-mediated lung inflammation, although Th2-mediated inflammation is more PKCθ-dependent [43].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation between function and topology of binding was observed in rats, mice, and humans [12, 20]. In rodents, CD28 superagonists induce immune deviation to Th2 [22] as well as expansion and functional activation of “natural” Treg cells [2325]. Accordingly, such mAb have high therapeutic efficacy in a wide range of rodent models of autoimmunity, inflammation, and allograft rejection [2531].…”
Section: Immune Deviation and Treg Activation With Stimulatory Cd28-smentioning
confidence: 94%
“…In this model of African trypanosomiasis, CD28SA treatment down-regulated IFNγ and TNF production by T-cells along with the production of reactive oxygen species by classically activated macrophages. Interestingly, it also triggered the development of alternatively activated macrophages, in line with a CD28SA-induced Th2 shift and IL-4 production [22]. With regard to pathology, CD28SA treatment delayed the onset of liver injury, diminished the anemia burden, and prolonged the survival of infected animals.…”
Section: Immune Deviation and Treg Activation With Stimulatory Cd28-smentioning
confidence: 99%